PENGARUH PENAMBAHAN BAKTERI ASAM LAKTAT TERHADAP KARAKTERISTIK KIMIA DAN ORGANOLEPTIK TEPUNG SORGUM FERMENTASI. - Seveline Seveline; Heni Oktafiana; Wijaya Murti Indriatama; Moh Taufik (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
The research aims to analyze the chemical and organoleptic properties of sorghum flour fermented by the addition of lactic acid bacteria. The study consisted of three stages, namely the preparation phase for the bacterial starter, the stage of making fermented sorghum flour and the analysis stage. The study consisted of four treatments namely one treatment of sorghum flour which was fermented spontaneously as a control and the other three sorghum flour fermented by the addition of Lactobacillus plantarum lactic acid bacteria, Lactobacillus fermentum and Lactobacillus paracasei. The fermentation process was carried out for 5 days, then the data were analyzed using one-way analysis of variants (ANOVA) at the 95% level with Duncan's further test. The results showed that the addition of lactic acid bacteria had no effect on water content, crude fiber content, tannin content, acidity (pH) value, panelist preference level on color, aroma and texture but had a significant effect on the level of panelist preference on overall sorghum flour resulting from.